2016
DOI: 10.1017/s0030605316000491
|View full text |Cite
|
Sign up to set email alerts
|

Who is killing the tiger Panthera tigris and why?

Abstract: We investigated the range of people involved in killing tigers Panthera tigris in the Bangladesh Sundarbans, their motives and methods, and their links to the commercial trade. Using snowball sampling we conducted  qualitative interviews with local people. We identified five categories (village residents, poachers, shikaris, trappers and pirates), each with different motives, methods and networks. Village residents kill tigers predominantly for safety, whereas others kill in the forest professionally or opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
(28 reference statements)
1
19
0
Order By: Relevance
“…Poaching remains a critical threat to the survival of many species worldwide, including tiger and rhino (Milliken & Shaw 2012;Saif et al 2016). The global conservation community, working through international bodies such as CITES, is committing significant resources to the fight against poaching as well as demand reduction measures (CoP16; Decision 16.85, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Poaching remains a critical threat to the survival of many species worldwide, including tiger and rhino (Milliken & Shaw 2012;Saif et al 2016). The global conservation community, working through international bodies such as CITES, is committing significant resources to the fight against poaching as well as demand reduction measures (CoP16; Decision 16.85, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Internet questionnaires were disseminated periodically on Twitter during a 49‐day period (26 December 2017 to 16 February 2018) via snowball sampling (Sadler et al 2010, Saif et al 2018). The survey emanated from an individual author's Twitter account, with information about the survey, its intent, and links to the survey provided, along with an image associated with each tweet.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have examined the last link of the poaching supply chain: the domestic markets in China (Moyle, 2009;Van Uhm, 2016;Van Uhm & Wong, 2019;Wong, 2016) and Nepal (Karmacharya et al, 2018). The first link, including the range of people involved, their motives and methods, and associated links to the commercial trade, have been examined in Bangladesh (Inskip et al, 2014;Saif et al, 2016Saif et al, , 2018, India (Sharma et al, 2014) and Sumatra (Risdianto et al, 2016;Shepherd & Magnus, 2004). Similar data does not exist in Russia.…”
Section: Case Selectionmentioning
confidence: 99%
“…Environmental factors (e.g., differences in terrain and accessibility), as well as variations in subspecies characteristics (e.g., behavior and population abundance) influences poaching pressure and the methods employed by poachers vary between subspecies and range countries. For example, in Sumatra, previous work has demonstrated that the most common poaching method is wire snares (Linkie et al, 2015;Risdianto et al, 2016); in Bangladesh there is a range of methods including poison, trapping, clubbing and sometimes shooting (Saif et al, 2018); in Thailand poachers have been known to poison carcasses of wild prey to lure and subsequently kill tigers (Duangchantrasiri et al, 2016. ) These examples highlight the context-specificity of wildlife crime even within a single species.…”
Section: Case Selectionmentioning
confidence: 99%
See 1 more Smart Citation